The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep38267
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin induces mitochondria-mediated apoptosis and enhances chemotherapeutic sensitivity of gastric cancer through reactive oxygen species

Abstract: The prognosis of gastric cancer remains poor due to clinical drug resistance. Novel drugs are urgently needed. Shikonin (SHK), a natural naphthoquinone, has been reported to trigger cell death and overcome drug resistance in anti-tumour therapy. In this study, we investigated the effectiveness and molecular mechanisms of SHK in treatment with gastric cancer. In vitro, SHK suppresses proliferation and triggers cell death of gastric cancer cells but leads minor damage to gastric epithelial cells. SHK induces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…In cancer cells, ROS are upregulated compared to normal cells [33]. However, contrary to tumor-promoting effects, cancer is more sensitive to ROS-induced apoptosis once ROS exceed certain physiological thresholds [17,29]. Therefore, increasing the intracellular ROS concentration is an effective anticancer strategy [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cancer cells, ROS are upregulated compared to normal cells [33]. However, contrary to tumor-promoting effects, cancer is more sensitive to ROS-induced apoptosis once ROS exceed certain physiological thresholds [17,29]. Therefore, increasing the intracellular ROS concentration is an effective anticancer strategy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing the intracellular ROS concentration is an effective anticancer strategy [20]. Previous reports have indicated that OXA-induced apoptosis is mediated by increased intracellular levels of ROS and the consequent mitochondrial apoptosis [3,[17][18][19]. In addition, H 2 S was highly associated with ROS resistance and AOAA upregulated ROS and P53 by inhibiting H 2 S synthesis [7,12,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, shikonin suppresses tumor growth in xenograft animal models and increases lipid peroxidation and apoptosis in vivo. Finally, shikonin enhances the antitumor activities of 5-fluorouracil and oxaliplatin in vivo [87]. Another natural compound of some fruits and vegetables with antitumoral properties in lung cancer, leukemia, and breast cancer is quercetin.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Shikonin is able to inhibit cell proliferation and induces apoptosis in several human malignancies such as gastric cancer [3], non-small cell lung cancer [4], pancreatic cancer [5] and so on. However, certain limitations exist, including no clear target and liver and kidney toxicity [6].…”
Section: Introductionmentioning
confidence: 99%